Notes to Philosophy 167: Class 13 -- Newton's De Motu Corporum in Gyrum (i.e. Version 1) -- Part 12. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Problem 3: The Inverse-Square Rule of Force -- Theorem 4: The Keplerian 3/2 Power Rule.; Generally corresponds to the video segment: Class 13, Part 12.